2020
DOI: 10.1002/dta.2903
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of epiandrosterone as a long‐term marker of testosterone use

Abstract: Identification and evaluation of long‐term markers is crucial in prolonging the detection window for anabolic steroid abuse in sport. Recently, sulfoconjugated epiandrosterone was identified as a potential long‐term marker for the abuse of certain endogenous anabolic agents, including testosterone, which continues to be widely used as a performance enhancing agent in sport. To evaluate the applicability of epiandrosterone sulfate as a marker for testosterone use, administration studies were conducted with mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…While this was true for subject 3 in this study, subject 8 did not show improved detectability in blood. Urine samples from subjects 1, 2, 6, 8, and 10 were also analyzed by GC/C/IRMS, and all subjects had more collections that were adverse by IRMS than identified by either profiling model 31 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While this was true for subject 3 in this study, subject 8 did not show improved detectability in blood. Urine samples from subjects 1, 2, 6, 8, and 10 were also analyzed by GC/C/IRMS, and all subjects had more collections that were adverse by IRMS than identified by either profiling model 31 …”
Section: Resultsmentioning
confidence: 99%
“…Urine samples from subjects 1, 2, 6, 8, and 10 were also analyzed by GC/C/IRMS, and all subjects had more collections that were adverse by IRMS than identified by either profiling model. 31…”
Section: Comparison With Urinary Steroidal Abp Valuesmentioning
confidence: 99%
“…This design allowed for a highly complex multivariate analysis of T treatment effects on serum and urine steroid profiles explaining 25.7% and 31%, respectively, of total variation. The models identified two main com- The present study investigated the effects of T administration on the carbon isotope ratio of T and 5α-diol, both shown previously to be the most informative for administration of transdermal T gel, 52,71 with the effects on 5α-diol due to the prominence of 5α-reductase expression in skin acting on T during its transdermal passage. Previous studies have investigated the potential of epiandrosterone sulfate as a long-term biomarker for androgen doping in men 8,52,72 including use of a single-oral dose of 50-mg DHEA in nine men 72 or transdermal T gel in two men taking 50-mg T applied topically for 7 days 8 and five men taking 40-mg T applied topically for 14 days.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14] In recent years, the diagnostic relevance of intact phase II metabolites was increasing, for example, shown for exogenous AASs like stanozolol and clostebol as well as for epiandrosterone-sulfate as a marker for misuse of testosterone and related endogenous steroids. [15][16][17][18][19][20][21][22][23] The investigation of the HepG2 cells as an adequate in vitro model to study and generate metabolites for doping analysis was the aim of the present study. The exogenous AAS metandienone, for which the biotransformation has been well studied over the last decades, was chosen as model substance.…”
Section: Introductionmentioning
confidence: 99%
“…Though Westerink and Schoonen as well as Gerets et al showed phase II enzyme expression in HepG2 cells, previous studies focusing steroid biotransformation investigated testosterone phase I metabolism solely 10–14 . In recent years, the diagnostic relevance of intact phase II metabolites was increasing, for example, shown for exogenous AASs like stanozolol and clostebol as well as for epiandrosterone‐sulfate as a marker for misuse of testosterone and related endogenous steroids 15–23 …”
Section: Introductionmentioning
confidence: 99%